Influence of anxiety symptoms on quality of life in idiopathic Parkinson´s disease without dementia (2023)
The Parkinson's Disease (PD) is a type of neurodegenerative pathology. It has a negative impact on the Quality of Life (QOL), the patient's daily life activities, as well as the psychological stability and family activities of their immediate caregivers.